PENDEKATAN MULTI-KRITERIA BERBASIS GIS UNTUK PENILAIAN RISIKO ESG PADA PEMBANGUNAN PLTA SEMENDE, SUMATERA SELATAN - Teguh Eko Sulistiyanto; Fajar Hendrasto; Suherma Dwi Nuryana; Benyamin; Moehammad Ali Jambak (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2026)
Run-of-river hydropower development has increasingly attracted attention as part of Indonesia's renewable energy transition. However, many projects encounter challenges due to insuffisient integration of sustainability aspects, particurlarly Environmental, Social, and Governance (ESG) considerations. Geohazard risks such as landslides, flash floods, and tectonic activity, along with environmental impacts including erosion, sedimentation, and land cover change, are often overlooked during the early planning stages. This research aims to develop a GIS-based ESG risk assement framework using a Multi Criteria Evaluation (MEC) approach. The variables considered include geohazard factors (slope, lithology, rainfall, active faults) environmental factors (land cover change, erosion potential, habitat conditions), and socio-economic factors (proximity to settlements, inftasructure, and land use patterns). The datasets used include Digital Elevation Model (DEM), geological maps, sattelite imagery, demographic and infrastructure data. The expected results are an ESG risk index and spatial risk maps that can prioritize sustainable sites for run-of-river hydropower development. This approach is anticipated to help developers, consutants, and policymakers identify projects that are not only technically and financially viable but also geohazard-reslient, environentally sound, and socially acceptable.